ANALISIS MAKNA DALAM VIDEO IKLAN ILM PENCEGAHAN STUNTING 60 DETIK PADA YOUTUBE KEMENTERIAN KESEHATAN RI - Nadia Itona Siregar (Kinesik, 2023)
Stunting is a global problem that continues to occur. From 2012 to 2022 the percentage of children under 5 years old affected by stunting in Indonesia is still in the high category. Most Indonesians do not understand the term stunting well, so education is needed for the community. Public service advertisements are one of the steps in educating the public massively. One is a public service advertisement by the Ministry of Health's YouTube account entitled ILM Pencegahan Stunting 60 Detik. This study aims to determine the meaning of public service advertisements through the Ministry of Health's YouTube channel titled ILM Pencegahan Stunting 60 Detik. The theories used in this research are mass communication theory and Roland Barthes's semiotic analysis. The research method used is the Roland Barthes semiotic method. The results showed that the meaning of the public service advertisement ILM Pencegahan Stunting 60 Detik is related to the role and participation of a father in assisting pregnant women and parenting children, where preventing stunting in infants and children requires cooperation between fathers and mothers. Furthermore, the video also tries to educate the public regarding myths circulating in Indonesia.